2007
DOI: 10.1021/jm0612158
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Cytotoxic Evaluation of a New Series of 3-Substituted Spiro[(dihydropyrazine-2,5-dione)-6,3‘-(2‘,3‘-dihydrothieno[2,3-b]naphtho-4‘,9‘-dione)] Derivatives

Abstract: A series of 3-substituted spiro[(dihydropyrazine-2,5-dione)-6,3'-(2',3'-dihydrothieno[2,3-b]naphtho-4',9'-dione)] derivatives were prepared using an easy synthetic route via condensation of the 3-amino-3-(ethoxycarbonyl)-2,3-dihydrothieno[2,3-b]naphtho-4,9-dione system and amino acids followed by intramolecular lactamization. Amino acids containing alkyl and aryl, linear and cyclic, polar and apolar, and basic and acid residues were incorporated. Evaluation of these analogues against the MCF-7 human breast car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 40 publications
4
35
0
Order By: Relevance
“…Previous work in our group on the synthesis of quinone-based cytotoxic agents, had confirmed that the incorporation of an indolizidindione moiety is an effective approach to devise new compounds with potential antitumor activity. 11 In this paper, we report a full account of our efforts towards the synthesis of a new series of diketopiperazine and spirooxoindolethiazolidine derivatives and the preliminary results of their biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in our group on the synthesis of quinone-based cytotoxic agents, had confirmed that the incorporation of an indolizidindione moiety is an effective approach to devise new compounds with potential antitumor activity. 11 In this paper, we report a full account of our efforts towards the synthesis of a new series of diketopiperazine and spirooxoindolethiazolidine derivatives and the preliminary results of their biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these naturally occurring naphthoquinones and their synthetic analogues are important precursors for the synthesis of natural products and pharmaceuticals [59]. The stereoselective formation of C–C bonds is of great importance for the synthesis of enantiomerically pure, biologically active organic compounds [1011].…”
Section: Introductionmentioning
confidence: 99%
“…Proliferation of research in spiro chemistry has now attained considerable height, right from the unprecedented synthesis of spiro hydrocarbon by Bayer [1]. Spiro heterocycles in particular fused at a central carbon atom display diverse biological and pharmaceutical [2–7] activities due to their interesting conformational features and structural implications. The presence of the sterically constrained spiro structure in various natural products also generates interest in the investigation on spiro compound [8, 9].…”
Section: Introductionmentioning
confidence: 99%